The Economics of Obesity Poverty, Income Inequality and Health - Alavi Hojjat, Tahereh; Hojjat, Rata.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2017)
This book offers a new perspective about the relationship of obesity to poverty and inequality providing a fascinating insight into the factors that influence individual choices regarding eating habits, diet and other behavioral patterns relevant to obesity. The authors explore a unique socioeconomic model that helps build the framework to understand the causes of obesity and its relation to health, science, and economics. An essential read for policy makers who are seeking a framework to address this problem.
1. Different Perspectives on Causes of Obesity -- 2. Consequences of Obesity -- 3. Economic Analysis: Behavioral Patterns and Diet Choice -- 4. Socioeconomic Factors: Poverty and Obesity -- 5. Income Inequality and Obesity -- 6. Data & Methodology: Obesity, Poverty and Income Inequality -- 7. Food Policy Interventions -- 8. Concluding Comments.
Keywords: Medicine; Health promotion; Health economics; Medical economics; Social structure; Social inequality; Medicine & Public Health; Health Promotion and Disease Prevention; Health economics; Social Structure, Social Inequality